Banyumas Tourism Mobile Application UI Design Using the User Experience Lifecycle - Nesya Dwinanda Sri Fadila; Gita Fadila Fitriana; Novian Adi Prasetyo (Universitas Teknokrat Indonesia, 2022)
Abstract−Internship became a must activity as a student in Institut Teknologi Telkom Purwokerto, but in its application, with many media looking for a place to work, students still have difficulty finding a suitable internship place. This study aims to apply Design Thinking and System Usability Scale for designing mobile apps interface to find internship place. Literature review used to find the basis for this research which was used for theories, basic concepts, and methods. Design Thinking is carried out to find a problem that students face. Validating issues was done by doing a survey. And prioritize the problem using challenge matrix. The prototype was done by creating a try-able design that users can try to reach the goal of design made, and test the successful rate using system usability scale. The result of this study is mobile apps design interface and tested using system usability scale with 8 test data had a success rate with value 93.75%. Interface design created can help students find the most suitable place for an internship that matches their skills and wishes.